Characteristics of Selected Components of Road Traffic Safety - Grzegorz SOBECKI; Robert PAWLICKI; Dominik ŁODEJ (Communications of International Proceedings, 2021)
This paper presents an analysis of selected factors shaping road traffic safety. The research was carried out on the example of Poland. Particular attention was paid to the process of testing future drivers and the adopted evaluation criteria, being the key elements affecting driving motor vehicles in line with the law. This has a direct impact on the safety of all users — be they pedestrians, cyclists, public transport passengers or individual drivers. In addition to cognitive purposes, the considerations carried out can be used for comparative analysis between other countries and drawing common conclusions on how to increase the road safety.
Keywords: Accidents; Road Traffic Safety; Causes Of Accidents